Simulation of patient-specific bi-directional pulsating nasal aerosol dispersion and deposition with clockwise 45° and 90° nosepieces. (August 2020) - Farnoud, Ali; Baumann, Ingo; Rashidi, Mohammad Mehdi; Schmid, Otmar; Gutheil, Eva
Abstract: Numerical simulations of the dispersion and deposition of poly-disperse particles in a patient-specific human nasal configuration are performed. Computed tomography (CT) images are used to create a realistic configuration of the nasal cavity and paranasal sinuses. The OpenFOAM software is used to perform unsteady Large Eddy Simulations (LES) with the dynamic sub-grid scale Smagorinsky model. For the numerical analysis of the particle motion, a Lagrangian particle tracking method is implemented. Two different nosepieces with clockwise inclinations of 45° and 90° with respect to the horizontal axis are connected to the nostrils. A sinusoidal pulsating airflow profile with a frequency of 45 Hz is imposed on the airflow which carries the particles. Flow partition analysis inside the sinuses show that ventilation of the sinuses is improved slightly when the 45° nosepiece is used instead of the 90° nosepiece. The flow partition into the right maxillary is improved from 0.22% to 0.25%. It is observed that a closed soft palate increases the aerosol deposition efficiency (DE) in the nasal cavity as compared to an open soft palate condition. The utilization of pulsating inflow leads to more uniform deposition pattern in the nasal airway and enhances the DE by 160% and 44.6%, respectively, for the cases with clockwise 45° and 90° nosepieces, respectively. The bi-directional pulsating drug delivery with the same particle size distribution and inflow rates as the PARI SINUS device results in higher total DEs with 45° nosepiece than with the 90°. Thus, the numerical simulation suggests that the 45° nosepiece is favorable in terms of the delivered dose. Graphical abstract: Image 1 Highlights: ∙ CFD simulations of pulsating bi-directional aerosol delivery (PBAD) in human nose ∙LES with dynamic SGS model combined with Lagrangian particle tracking ∙Enhancement of the total deposition efficiency (DE) of particles using PBAD ∙Higher DE with PBAD compared to non-pulsating bi-directional aerosol delivery ∙Improved DE in PBAD with a clockwise 45° nosepiece compared to a 90° nosepiece